Leaf Morphology and Ontogeny Kembang Semangkok (Scaphium Macropodum) From Gunung Leuser National Park (TNGL)-North Sumatra. (May 2020) - Susilowati, A; Elfiati, D; Batu, S A L; Rachmat, H H; Ginting, I M
Abstract: Scaphium macropodum or malvanut or locally known as Kembang semangkok was member of Sterculiacease those well adapted under closed canopy stratum. The species was targeted for illegal logger due to its valuable seed that has many benefits for medicinal purposes and the wood for building and construction. This extraction causing Kembang semangkok classified at least concern according to IUCN redlist. Lack information on the existence and morphology on Kembang semangkok in North Sumatra, causing confusing identification in the field. Therefore, our research was conducted to identify leaf morphology and assumed ontogeny of Kembang semangkok originated from Gunung Leuser National Park. The research was conducted through survey method on 9 (nine) plot of Kembang semangkok. Observation and measurement for morphology were carry out on leaf organ those were leaf shape, leaf arrangement, leaf composition, leaf margin, leaf base, leaf blade and leaf apex. Our research showed that ontogenic change was found in Kembang semangkok due to their respond to survival and plant growth. The changes can be identified by leaf shape from entire (under 50 cm height) into palmed-parted leaf (taller than 50 cm) and returned onto entire after 12 m height.